2005
DOI: 10.1111/j.1468-0491.2005.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating International Food Standards: The World Trade Organization's Impact on the Codex Alimentarius Commission

Abstract: The article presents an empirical account of how the role, position, and perception of the intergovernmental food standardization body, Codex Alimentarius Commission, has changed after being referred to by the World Trade Organization (WTO) as the “central reference point for the elaboration of international food standards.” Both the Sanitary and Phytosanitary Measures Agreement and the Technical Barriers to Trade Agreement include provisions that encourage WTO members to base their national regulations on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(38 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…A growing number of studies have shown that interaction among regimes and/or clusters of institutions is deepening and producing uncertainty for actors (Raustialia and Victor, 2004). Heightened uncertainty may lead to new cooperation and coordination problems, such as constraining or chilling effects by one institution on another (Conca, 2000;Eckersley, 2004;Axelrod 2011 in Oberthur and Stokke;Veggeland and Borgen, 2005;Oberthür and Gehring, 2006) or 'spillovers' effects that can reinforce fragmentation and regime integration/ separation dynamics (Biermann et al, 2009;Johnson and Urpelainen, 2012). Uncertainty also creates opportunities for policy entrepreneurs and new ideas to enter global policy spaces that may set governance along new pathways.…”
Section: The Complexity Of Transnational Governancementioning
confidence: 99%
“…A growing number of studies have shown that interaction among regimes and/or clusters of institutions is deepening and producing uncertainty for actors (Raustialia and Victor, 2004). Heightened uncertainty may lead to new cooperation and coordination problems, such as constraining or chilling effects by one institution on another (Conca, 2000;Eckersley, 2004;Axelrod 2011 in Oberthur and Stokke;Veggeland and Borgen, 2005;Oberthür and Gehring, 2006) or 'spillovers' effects that can reinforce fragmentation and regime integration/ separation dynamics (Biermann et al, 2009;Johnson and Urpelainen, 2012). Uncertainty also creates opportunities for policy entrepreneurs and new ideas to enter global policy spaces that may set governance along new pathways.…”
Section: The Complexity Of Transnational Governancementioning
confidence: 99%
“…The agreement gives these standardization bodies a more significant role to play. This is particularly true for the Codex Alimentarius Commission, whose standards have been an issue in several WTO trade disputes (Veggeland and Borgen 2005). Since 1962, the Codex has been responsible for managing the Joint Food Standards Programme of the Food and Agriculture Organization of the United Nations (FAO) and the World Health Organization (WHO) (FAO/WHO 1999).…”
Section: The European Commission and The External Representation Of Tmentioning
confidence: 99%
“…WTO members can fulfil their obligations under this agreement by basing their national regulations on international standards (Veggeland and Borgen 2005). In this context, the SPS Agreement refers to three international standardization bodies: the OIE (animal health), IPPC (plant health) and Codex Alimentarius Commission (food safety).…”
Section: The European Commission and The External Representation Of Tmentioning
confidence: 99%
“…This paper reviews the history of carrageenan from the time that it began to be industrially manufactured for food use in the US to the present. While differences still exist, there has been a growing move in recent years towards international harmonisation of food 4 regulation through the Codex Alimentarius system and the EU Commission (Garrett et al, 1998;Livermore, 2006;Millstone et al, 2002;Veggeland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%